Mean platelet volume in preterm infants as a predictor of late-onset neonatal sepsis: a retrospective comparative study - Abigail Goshen; Tzipora Strauss; Leah Leibovitch; Hagar Zohar; Ayelet Gavri-Beker (BMJ Paediatrics Open)
Background Neonatal sepsis remains a primary cause of morbidity and mortality among newborns. Rapid and accurate diagnosis poses a significant challenge—the non-specific clinical presentation of neonatal sepsis relies heavily on various laboratory indices for early detection and subsequent management. One such indicator under investigation is the mean platelet volume (MPV), which may serve as a predictive marker. This study aims to evaluate the association between the MPV and late-onset sepsis in preterm infants.Methods This retrospective study included 63 newborns born at Sheba Medical Center from 2016 to 2020 with late-onset sepsis as evidenced by positive blood cultures, and 63 newborns in the control group. We analysed blood count data at three intervals: preinfection, intrainfection and postinfection. Electronic medical records provided supplemental data. Each septic neonate was paired with a non-septic control.Results Our results revealed a significant elevation of MPV in septic newborns compared with non-septic controls during the days prior to the infection (9.323 and 8.876, respectively, p=0.043) and persisted up to 2 weeks postinfection (9.39 vs 8.714, p=0.025).The MPV and the MPV-to-total platelet (PLT) count ratio exhibited significant predictive capabilities in receiver operating characteristics analysis (−0.60 and −0.57, respectively).Conclusions High MPV in combination with PLT decrement might be predictive for the diagnosis of late-onset sepsis. Future studies should be conducted in order to better understand the underlying pathophysiology and the potential clinical applications of these findings.